Dystans i pragnienie bezpośredniości: nowoczesna świadomość Bolesława Leśmiana - Winiecka, Elżbieta (Poznańskie Studia Polonistyczne. Seria Literacka, 2009)
The article presents B. Leśmian as a poet involved in his self-imposed task of promoting a return to primeval nature, but, at the same time, somebody who is fully aware of the utopian character of thus formulated and adopted assumptions. The two contradictory approaches converge in a poetic figure of desire. This particular urge is treated as a model of the imagination of the poet, who creates his poetical world knowing that the ultimate aim is unattainable but constitutes the ideal of poetry and can only be a state of cognitive assurance and self-knowledge or, alternatively, a situation of ontological stability and fulfilment. However, to reach this utmost goal, either on the poetical plane or on the existentialist, epistemological and ontological plane, to fulfill the cherished desires, is not possible within the poetical world created by Leśmian. The raison d’etre of the self manifested by the protagonists of his poems as well as a justification of this poetry is the very striving towards the goal. The article shows the relevant dimensions of that desire as a metapoetical figure, anthropological and existentialist figures and epistemological and ontological figures. It further presents the opposition and the inner conflict within the modern views of the poet, who, consciously inscribes into his project its impracticability. The distance towards the current times and towards the idealistic assumptions of his own poetical programme constitutes the intrinsic originality of Leśmian’s poems.